FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PETANI TERHADAP PROGRAM PENANAMAN PADI GOGO DI KECAMATAN TABA PENANJUNG KABUPATEN BENGKULU TENGAH - Mardila, Shovia Alkesya; Tri Wahyuni Damayanti; Sazuli; Susila Isma (Universitas Ratu Samban, 2025)
This study aims to analyze farmers' perceptions of the upland rice planting program in Taba Penanjung District, Central Bengkulu Regency, with a primary focus on the economic aspect and to identify the factors influencing it. The research method used a quantitative descriptive approach with data collection techniques through questionnaires and interviews. A sample of 52 farmers was selected using purposive sampling and simple random sampling methods. Data analysis was conducted using a Likert scale, the successive interval method (MSI), and multiple linear regression. The results showed that farmers' perceptions of the upland rice planting program were categorized as good (73%), with the economic aspect being the most dominant aspect influencing farmers' decisions. Factors such as age, last education, farming experience, number of family members, and land area significantly influenced farmers' perceptions, where all variables had a negative relationship. The economic aspect emphasized the importance of seed assistance, fertilizer, and access to loans to increase farmers' productivity and income. This study recommends increasing economic support from the government for the sustainability of the upland rice program as an alternative for food security.